The Association between Workload of Frontline Health Workers and The Risk of Perceived Stress During COVID-19 Mass Vaccination: A Cross-Sectional Survey - Hikmah, Kholishotul; Helda, Helda; Melinda, Gea; Ayatullah, M. Ibraar; Prisandy, Lucky (Yayasan Ahmad Mansyur Nasirah, 2025)
The COVID-19 pandemic has had an unprecedented impact on mental heath, and in particular on health workers on the frontlines of pandemic response efforts, particularly in the context of COVID-19 vaccination. This study aimed to highlight the association of workload and adverse stress impact on healthcare workers during COVID-19 mass vaccination and its contributed factors. The method use a cross-sectional survey using a web-based questionnaire was conducted from the end of July to the beginning of August 2021. Participants were selected from all health facilities in Indonesia, with the minimal sample size 345 required. Logistic regression was performed using STATA 16.0 to assess the association between workload and perceived stress. This study revealed that prevalence of perceived stress was 36.2% among total of 447 eligible subjects. Health workers who had high-relatively levels of workloads (OR=1.76; 1.00-3.09) and without history of stress diagnosis (OR=5.23; 1.06-5.87) were more likely to develop perceived stress. The high level of workload was associated inversely with a decreased risk of stress according to age and stress diagnosis. The conclusions is a decreased risk of stress associated with workload among health professionals.